Harvesting Optimization, Biomass, and Lipid Content Analysis of Euglena sp. Culture with Ettlia texensis Bioflocculant and Commercial Chitosan - Eko Agus Suyono; Siti Mudrikah; Khalid Erlangga Karilanata; Dedy Kurnianto; Arief Budiman; Nugroho Dewayanto; Renata Adaranyssa Egistha Putri; Brilian Ryan Sadewo; Tia Erfianti (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract